Assessing the impact of an educational intervention program on sexual abstinence based on the health belief model amongst adolescent girls in Northern Ghana, a cluster randomised control trial - Ibrahim Yakubu; Gholamreza Garmaroudi; Roya Sadeghi; Azar Tol; Mir Saeed Yekaninejad; Adadow Yidana (2019)
Adolescent pregnancy is a worldwide problem because of its health, social, economic and political repercussions on the globe. Even though the rates of adolescent pregnancy have declined over the decade, there is still unacceptably high rates especially in lower and middle-income countries including Ghana. Although the problem has been widely investigated, there is little information on the effectiveness of different methods to improve adolescent sexual abstinence based on theoretical models. This study is aimed to assess an educational intervention program on sexual abstinence based on the Health Belief Model (HBM) among adolescent girls in Northern Ghana. A cluster randomized control trial was conducted in Ghana from April to August 2018. Participants within the ages of 13–19 years were enrolled voluntarily from six randomly selected Senior High Schools (3 for intervention and 3 for control). A total of 363 adolescent were enrolled. A self-structured questionnaire was administered to both groups of participants at baseline and endpoint of the study. Control participants received their normal classes whiles the intervention group additionally received comprehensive sexuality education for 1 month. Qualified midwives conducted the health education program. At least two sessions were conducted for each participating class weekly. The lessons focused on perceived susceptibility, perceived severity of adolescent pregnancy, perceived benefits, perceived barriers to adolescent pregnancy prevention, personal and family values, perceived self-efficacy and knowledge of contraceptives. Educational strategies such as discussions, demonstrations, role-play and problem solving techniques were used to deliver the lessons. Sexual abstinence was the outcome variable of the study and it was measured after 3 months of the intervention. Binary logistic regression was used to assess the impact of the intervention on sexual abstinence practice. At baseline, there was no difference between control and intervention groups. The mean score of Knowledge and attitude for control were (58.17 and 139.42) and intervention (60.49 and 141.36) respectively. Abstinence practice was 69.4% for control and 71.6% in the intervention group. However, after the intervention, the mean score of knowledge and attitude for control were (87.58 and 194.12) respectively. Sexual abstinence in the control was 84.4% and intervention was 97.3% respectively. The educational interventions resulted in a significant difference in sexual abstinence between intervention and control groups (OR = 13.89, 95% Confidence Interval (2.46–78.18, P < 0.003). Educational intervention, which was guided by HBM, significantly improved sexual abstinence and the knowledge of adolescents on pregnancy prevention among the intervention group. Provision of comprehensive sex education guided by behavioural theories to adolescents at Senior High Schools in Ghana is recommended. This trial was retrospectively registered in Protocol Registration and Results System (PRS) with trial number NCT03384251 .